2010
DOI: 10.1175/2010jpo4167.1
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Detachment Process of the Low-Salinity Water around Changjiang Bank in the East China Sea

Abstract: A patchlike structure of low-salinity water detached from the Chanjiang ''Diluted Water'' (CDW) is frequently observed in the East China Sea (ECS). In this study, the offshore detachment process of CDW into the ECS is examined using a three-dimensional numerical model. The model results show that low-salinity water is detached from the CDW plume by the intense tide-induced vertical mixing during the spring tide period when the tidal current becomes stronger. During the spring tide, thickness of the bottom mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 37 publications
12
74
1
Order By: Relevance
“…In this period tides around the Changjiang Bank also have their largest tidal range (sea level amplitude is approximately 1.6 m) because of spring tides. These conditions for the CDW's detachment may support the interpretation of Moon et al (2010) for the detachment process around the Changjiang Bank. They suggested that the offshore detachment of CDW occurs in the sloping side of the Changjiang Bank where the tidal energy dissipation is strong enough to overcome the buoyancy effect during spring tide.…”
Section: Low-salinity Water Detached From Main Cdw Plumesupporting
confidence: 68%
See 2 more Smart Citations
“…In this period tides around the Changjiang Bank also have their largest tidal range (sea level amplitude is approximately 1.6 m) because of spring tides. These conditions for the CDW's detachment may support the interpretation of Moon et al (2010) for the detachment process around the Changjiang Bank. They suggested that the offshore detachment of CDW occurs in the sloping side of the Changjiang Bank where the tidal energy dissipation is strong enough to overcome the buoyancy effect during spring tide.…”
Section: Low-salinity Water Detached From Main Cdw Plumesupporting
confidence: 68%
“…11. This shows that both the intense tide-induced vertical mixing and winddriven cross-shelf transport largely contribute to the detachment process of the CDW (Moon et al 2010). …”
Section: Low-salinity Water Detached From Main Cdw Plumementioning
confidence: 86%
See 1 more Smart Citation
“…In summer (Fig. 5c), tidal currents shift the core of the plume slightly to the south of Changjiang mouth and therefore bring the model result closer to observations (e.g., Moon et al 2010). The northward intrusion into the Yellow Sea is much reduced.…”
Section: Changjiang Plume Dispersalsupporting
confidence: 61%
“…A few intermediate models Rong and Li 2012) examined interactions between Changjiang plumes and tides in the absence of mean circulation. Moving one step further, Moon et al (2010) and Wu et al (2011) included the mean shelf circulation in addition to river and tidal forcing, focusing on how tides induce the offshore detachment of Changjiang plume in summer. By including tides, the modeled summer intrusion of Changjiang plume into the Yellow Sea is much reduced, bringing the modeled plume dispersal closer to reality (Wu et al 2011).…”
Section: Introductionmentioning
confidence: 99%